2021
DOI: 10.1051/0004-6361/202141333
|View full text |Cite
|
Sign up to set email alerts
|

Polarised emission from aligned dust grains in nearby galaxies: Predictions from the Auriga simulations

Abstract: Context. Polarised emission from non-spherical dust grains contains information about the alignment of these dust grains and traces the structure of the interstellar magnetic field. Methods. We post-processed a set of Milky-Way-like galaxies from the Auriga project, assuming a dust mix consisting of spheroidal dust grains that are partially aligned with the model magnetic field. We constrained our dust model using Planck 353 GHz observations of the Milky Way. This model was then extrapolated to shorter wavelen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…We obtained an average value of the LMC polarization fraction of 5.1%. We use results from recent simulations by Vandenbroucke et al (2021) to show that this is lower than the expected value for a galaxy similar to ours observed faced-on at the distance of the LMC. The maximum polarization value we observe is however significantly higher than the expected value from those simulations (13%).…”
Section: Summary and Perspectivesmentioning
confidence: 64%
See 2 more Smart Citations
“…We obtained an average value of the LMC polarization fraction of 5.1%. We use results from recent simulations by Vandenbroucke et al (2021) to show that this is lower than the expected value for a galaxy similar to ours observed faced-on at the distance of the LMC. The maximum polarization value we observe is however significantly higher than the expected value from those simulations (13%).…”
Section: Summary and Perspectivesmentioning
confidence: 64%
“…XIX 2015), the difference in column density may explain the slightly lower maximum polarization fraction observed here for the LMC. Vandenbroucke et al (2021) simulated polarimetric observations of external galaxies, including dust properties, alignment, radiative transfer and spiral magnetic field geometries with different inclination angles, based on the MHD structure predicted by the Auriga simulations. The model, when observed from within the simulated galaxy, was constrained using the Planck data and was used to derive linear polarization fractions that could have been observed with the SPICA/B-BOP instrument.…”
Section: Polarization Fraction and Polarized Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in their polarized spectrum is expected as the optical depth decreases with wavelength, producing an increase in thermal polarized emission. Interestingly, Vandenbroucke et al (2021) showed a polarized spectrum with a dip in the 60−90 µm wavelength range. They assumed a linear mixture of perfectly aligned silicate dust grains and non-aligned graphite dust grains.…”
Section: Polarized Spectrum Of Starburst Galaxiesmentioning
confidence: 99%
“…Представление реальных рассеивателей сфероидами является подходом, широко применяемым в разных областях науки: например, в оптике атмосферы [1][2][3], астрономии [4], медицине [5], нанооптике [6], лабораторном анализе [7] и т. д. Особенно часто используется сфероидальная модель в современной астрофизике из-за отсутствия информации о форме несферических космических пылинок [8][9][10][11][12].…”
Section: Introductionunclassified